185k views
17 votes
10x + 7y = –8
7x + 7y = –14

User Xorspark
by
5.7k points

1 Answer

9 votes

Answer:

(2, - 4 )

Explanation:

Given the 2 equations

10x + 7y = - 8 → (1)

7x + 7y = - 14 → (2)

Subtract (2) from (1) term by term to eliminate y

(10x - 7x) + (7y - 7y) = - 8 - (- 14) , that is

3x = 6 ( divide both sides by 3 )

x = 2

Substitute x = 2 into either of the 2 equations and solve for y

Substituting into (1)

10(2) + 7y = - 8

20 + 7y = - 8 ( subtract 20 from both sides )

7y = - 28 ( divide both sides by 7 )

y = - 4

solution to the system of equations is (2, - 4 )

User Adrian Chen
by
5.3k points